Zadacha Kuznecov Predely 10-25

Материал из PlusPi
Перейти к: навигация, поиск

Условие задачи

Вычислить предел функции:

<math>\lim_{x\to 0} \frac{\sqrt{1-2x+3x^2} -(1+x)}{\sqrt[3]{x}}</math>

Решение

<math>\lim_{x\to 0} \frac{\sqrt{1-2x+3x^2} -(1+x)}{\sqrt[3]{x}} = </math>
<math> = \lim_{x\to 0} \frac{\left(\sqrt{1-2x+3x^2} -(1+x)\right)\left(\sqrt{1-2x+3x^2} +(1+x)\right)}{\sqrt[3]{x}\left(\sqrt{1-2x+3x^2} +(1+x)\right)} = </math>
<math> = \lim_{x\to 0} \frac{1-2x+3x^2 -(1+x)^2}{\sqrt[3]{x}\left(\sqrt{1-2x+3x^2} +1+x\right)} = \lim_{x\to 0} \frac{1-2x+3x^2 -(1+2x+x^2)}{\sqrt[3]{x}\left(\sqrt{1-2x+3x^2} +1+x\right)} = </math>
<math> = \lim_{x\to 0} \frac{1-2x+3x^2 -1-2x-x^2}{\sqrt[3]{x}\left(\sqrt{1-2x+3x^2} +1+x\right)}= \lim_{x\to 0} \frac{-4x+2x^2}{\sqrt[3]{x}\left(\sqrt{1-2x+3x^2} +1+x\right)} = </math>
<math> = \lim_{x\to 0} \frac{x(2x-4)}{\sqrt[3]{x}\left(\sqrt{1-2x+3x^2} +1+x\right)} =\lim_{x\to 0} \frac{\sqrt[3]{x^2}(2x-4)}{\sqrt{1-2x+3x^2} +1+x} = </math>
<math> = \frac{\sqrt[3]{0^2}(2\cdot 0-4)}{\sqrt{1-2\cdot 0+3\cdot 0^2} +1+0} = \frac{0}{1+1} = 0 </math>